Reframing Power in New Ventures: A Literature Synthesis on Capital Diversity and Strategic Influence Among Founders and Investors - Muhammad Rizal; Farah Qalbia (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This qualitative literature review explores how various forms of capital—beyond financial investment—shape power dynamics between founders and investors in new ventures. Drawing on organization theory, entrepreneurship, and governance literature, the review synthesizes findings on human, social, reputational, and symbolic capital as sources of strategic influence. It challenges the traditional dominance of financial capital in venture control and highlights how non-financial assets enable founders to assert influence, co-create governance, and navigate investor relations. The analysis reveals that power in new ventures is dynamic, relational, and context-dependent, offering a reframed understanding that informs both academic theory and entrepreneurial practice